A Comparison of Creative Thinking Skills in Digestive System Learning Based on Learning Styles: Komparasi Keterampilan Berpikir Kreatif pada Materi Sistem Pencernaan Ditinjau dari Gaya Belajar - Erika Avenda Khaznah; Dyah Astriani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Creative thinking skills are necessary in science education in the 21st century, but their achievement is often unevenly influenced by student characteristics, such as learning styles. This quantitative research with a survey design aims to describe and compare students' creative thinking skills in digestive system material in terms of learning style differences. The research subjects consisted of 52 eighth-grade students at Muhammadiyah 13 Panceng Junior High School in the 2025/2026 academic year. The data collection instruments were a validated essay test and a learning style questionnaire. Data analysis showed that the fluency indicator achieved the highest criteria, while the elaboration indicator achieved the lowest. In terms of learning styles, visual learners tended to have superior creative thinking skills compared to other learning styles. This indicates that digestive system material provides cognitive advantages for visual learners. Thus, there is a correlation between learning styles and students' creativity levels. So educators are advised to design differentiated learning strategies to optimize students' creative potential.